Luminescence properties of GdAl3(BO3)4: Dy3+ phosphors for white-LEDs. (2016) - Jamalaiah, B.C.; Nayab rasool, Sk.
Abstract: Different concentrations of Dy 3+ -doped GdAl3 (BO3 )4 phosphors were synthesized by solid state reaction method at different calcination temperatures. The phosphors calcined at 1100°C for 5 hours were crystallized into rhombohedral GdAl3 (BO3 )4 structure. Upon 352 nm excitation, the studied phosphors show the Dy 3+ characteristic emission transitions, 4 F9/2 → 6 H15/2, 4 F9/2 → 6 H13/2, 4 F9/2 → 6 H11/2 . The novelty in the studied phosphors is that the titled phosphors crystallized into nanophase and exhibit white luminescence when excited with 352 nm wavelength. The experimental results suggest that the GdAl3 (BO3 )4 :Dy 3+ phosphors are potential for white LED applications.